Wide Area BonjourGrid as a Data Desktop Grid: Modeling and Implementation on Top of Redis - Saad, Walid; Abidi, Leila; Abbes, Heithem; Cérin, Christophe; Jemni, Mohamed (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2014: Anais do XXVI International Symposium on Computer Architecture and High Performance Computing, 2014)
Desktop Grid is among the success stories during last years by using volunteers nodes participating into projects. Now, with the emergence of Cloud Computing, the questions become where to take resources? and how to coordinate the resources? Our assumption is that Desktop Grid will continue to survive if we are able to transform the old-fashioned client/server architecture to new web oriented architecture to deliver services on demand. This paper revisits and extends the coordination protocol of BonjourGrid, a decentralized desktop grid system, based on the Publish-Subscribe paradigm and including a new tier for data management. The new protocol is designed according to a formal modelling using colored Petri nets. The protocol is veried and proved by CPN-Tools and implemented with Redis, a polpular net technology. We conducted out experiments on the Grid'5000 testbed using 300 nodes. We analyze the Redis performance and we demonstrate that the extended version of BonjourGrid system is fully operational.